EFEKTIVITAS PENYALURAN BANTUAN JARING PENGAMAN SOSIAL (JPS) DI PROVINSI BANTEN - Yusniah Anggraini Yusnia; Guntur Fernando (Badan Penelitian dan Pengembangan Provinsi Kalimantan Barat, 2023)
Realizing that the pandemic does not only affect the health sector, the government has adopted a social safety net (JPS) policy for the lower strata of society. However, JPS is often off-target due to inaccurate beneficiary data. In Banten Province, the distribution of social assistance in 2020 needs to be improved by recipient data. The transfer of Banten Provincial Government's regional treasury from Bank Banten to BJB impacted the delay in distributing assistance to the community. Therefore, this study will analyze the effectiveness of the JPS distribution method in handling the impact of the Covid-19 pandemic in Banten Province, focusing on assistance allocated from the Banten Provincial Government's APBD. This research uses a qualitative approach. The data were collected using observation, interview, and documentation methods. Primary data came from interviews and questionnaires with respondents selected purposively (purposive sampling). The results of the study concluded that the provision of JPS social assistance was sufficient to help maintain the community's purchasing power. However, it has not been able to create social welfare. From the targeting aspect, the provision of JPS social assistance was generally on target, although there were still various data collection problems. Banten Provincial Government needs to evaluate the Beneficiary Families (KPM)from the Non-DTKS data. Furthermore, the Banten Provincial Government must change the pattern of determining KPM to a bottom-up approach that provides input to the decision-makers above. The synergy between the government and the bank as the channeling service must continue to be strengthened.